DAMPAK KEBIJAKAN FISKAL UNTUK SUBSIDI PANGAN TERHADAP EKONOMI, DISTRIBUSI PENDAPATAN DAN KEMISKINAN - taufikkurahman kurahman (Universitas Djuanda Bogor, 2011)
The fiscal policy of in the form of food subsidy that had been set by the government contained in Budget of the State. The main problem is the effort to respond to a variety of policy issues on agriculture subsidies that encourage changes in economic growth, the amount of labour absorption, income distribution, and poverty in rural and urban households. The study aimed to analyse the impact of fiscal policy on major issues above. CGE approach is a method of analysis used. The analysis showed that the impact fiscal policy in the form of food subsidies to the economy, especially macroeconomic indicators to improve national economic growth in both the short and long term; gives a higher impact of the increasing number of employment categories in the sectors of agriculture and agriculture-based industries in both urban and rural areas. That policy has a number of labour absorption capacity and increased real income at the household level in rural and urban areas for short and long term. The impact on poverty when viewed from the poverty incidence, poverty depth and severity of poverty shows that, in the short and long term shows households poverty reduction in the rural areas tend to be higher than the households poverty reduction in urban areas. The implication is food subsidy policy is quite effective in improving income distribution and poverty reduction especially in rural households. This suggests that in order for effective implementation of this policy is better, it is necessary to improve market structures in both the rural and urban areas. Efforts to increase the absorption of the workforce and reduce inequality of income distribution at household level in rural and urban areas is necessary to improve the macro-economic growth through a combination of a variety of other fiscal policies, especially fiscal policy in the agricultural sector.